Model Matematika Jumlah Perokok yang Dipengaruhi Faktor Migrasi dengan Dinamika Akar Kuadrat pada Kondisi Relapse - Tria Agus Krisan; Media Rosha (UNIVERSITAS NEGERI PADANG, 2020)
Abstract—Smoking is a habit that some people likes, but it causes health, economic, social, andenvironmental burdens not only for smokers but also for others. This study describes a mathematical model of the number of smokers which is influenced by the distribution factor of smokers using the dynamics of the square root in the relapse condition. The population was divided into three subpopulations, namely potential smokers, light smokers and heavy smokers. Based on the results of model analysis, it was found that one endemic equilibrium point of smokers was stable. Environmental influences make there always interactions between potential smokers and light smokers so that there are always smokers. The smaller the interaction between potential smokers and light smokers, the smaller the number of light smokers and heavy smokers. Keywords—Mathematical Model, Smoker Population,Asymptotically Stable, Equilibrium Point.